'The other boys of Kilmichael': No. 2 Section, 'C' Company, Auxiliary Division Royal Irish Constabulary, 28 November 1920. Issue 238 (12th March 2014) - Nelson, Andrew
Abstract The Kilmichael incident of November 1920, in which an Irish Republican Army (I.R.A.) column of nearly forty men ambushed and killed all bar one of a motorized patrol of eighteen Auxiliary Division Royal Irish Constabulary cadets, proved to be one of the I.R.A.'s most noted victories of the Anglo‐Irish War. Recent historiography has been dominated by controversy over the late Peter Hart's 1998 conclusion that contemporary British claims of I.R.A. mutilation of the cadet's dead bodies were true. However, this article aims to demonstrate that studying other aspects of Kilmichael, such as the British unit, can enable a broader understanding of both the ambush, and of contemporary British policy concerns.